Effects of visual gait-retraining on different running conditions and speeds - Liebenberg, J. N.; Witt, M. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
In running athletes suffer a certain amount of injuries in a given year. Gait-Retraining therefore has been a proposed method to decrease impact loads in runners. Consequently, the purpose of this study was to confirm the effectiveness of gaitretraining, observe kinematic changes and establish transfer between overground (OG) and treadmill (TD) running as well as different velocities. Results confirmed that gaitretraining can reduce tibial impact shock. This was found during TD running (pre/post) across 3 different speeds with lower effect in OG running. Kinematics changes were found in footstrike (TD and OG), ankle (TD) and trunk (TD) angles. To increase transfer effects, we should poof new methods for motor learning and/or improve the devices for feedback training in overground running.